2019
DOI: 10.3390/ijms20163887
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Chemerin and Its Receptors in the Porcine Hypothalamus and Plasma Chemerin Levels during the Oestrous Cycle and Early Pregnancy

Abstract: Chemerin (CHEM) may act as an important link integrating energy homeostasis and reproductive functions of females, and its actions are mediated by three receptors: chemokine-like receptor 1 (CMKLR1), G protein-coupled receptor 1 (GPR1), and C-C motif chemokine receptor-like 2 (CCRL2). The aim of the current study was to compare the expression of CHEM and its receptor (CHEM system) mRNAs (quantitative real-time PCR) and proteins (Western blotting and fluorescent immunohistochemistry) in the selected areas of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Data from literature indicates that this new class of markers could be chemerin and irisin (Khan, 2018;Smolinska et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Data from literature indicates that this new class of markers could be chemerin and irisin (Khan, 2018;Smolinska et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies have shown the presence of all three CHEM-associated receptors in selected structures of the pig hypothalamus [16] and ovary [17] during the estrous cycle and early pregnancy, which allowed us to conclude that CHEM has a direct effect on the hypothalamic-pituitary-gonadal regulatory axis (HPG) by modifying the functioning of its upstream structures. We hypothesized that CHEM may have endocrine effects on downstream structures of the HPG axis, in particular on CL producing steroid hormones, significantly modifying reproductive processes in mammals.…”
Section: Introductionmentioning
confidence: 92%
“…After washing, LC were cultured for 24 h in F-12 medium with BSA (1%) and antibiotics, with or without recombinant human CHEM in concentration 200 ng/mL of medium. The concentration of the factor was selected on the basis of its relatively high level in women and porcine blood plasma [16,20].…”
Section: Isolation Of the Luteal Cells And In Vitro Cell Culturesmentioning
confidence: 99%
“…The expression of the chemerin system (a collective term for chemerin and its receptors) was confirmed in brain structures responsible for reproductive functions, as well as in the lower branches of the hypothalamic-pituitary-ovarian axis and the female reproductive tract. Chemerin expression was confirmed in the hypothalami of mice and pigs [ 13 , 14 ]. Chemerin receptor expression was reported in porcine and bovine pituitaries and hypothalami [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%